2020
DOI: 10.20945/2359-3997000000214
|View full text |Cite
|
Sign up to set email alerts
|

The rs11755527 polymorphism in the BACH2 gene and type 1 diabetes mellitus: case control study in a Brazilian population

Abstract: Objective: Type 1 diabetes mellitus (T1DM) is an autoimmune disorder caused by a complex interaction between environmental and genetic risk factors. BTB domain and CNC homolog 2 (BACH2) gene encodes a transcription factor that acts on the differentiation and formation of B and T lymphocytes. BACH2 is also involved in the suppression of apoptosis and inflammation in pancreatic beta-cells, indicating a role for it in the development of T1DM. Therefore, the aim of this study was to evaluate the association of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al 51 , Zhang et al 52 , Hartz et al 53 , Słomiński et al 54 , Johansson et al 55 , Pan et al 56 , Lopez-Sanz et al 57 , Grant 58 , Słomiński et al 59 , Galán et al 60 , Jordan et al 61 , Winkler et al 62 , Yip et al 63 , Crookshank et al 64 , Lempainen et al 65 , Qu and Polychronakos 66 , Morrison et al 67 , Zhang et al 68 , Gerlinger-Romero et al 69 , Belanger et al 70 , Dieter et al 71 , Wanic et al 72 , Ushijima Wanic et al 73 , Guo et al 74 , Davis et al 75 , Elbarbary et al 76 , Villasenor et al 77 , Zhang et al 78 , Lee et al 79 , Zhi et al 80 , Li Calzi et al 81 , Sebastiani et al 82 , Cherney et al 83 , Doggrell 84 and Yanagihara et al 85 studied the clinical and prognostic values of FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N -methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 in patients with T1DM. Vassilev et al 86 , Qin et al 87 , Ma et al 88 , West et al 89 , Hoffmann et al 90 , Deary et al 91 , Belangero et al 92 , Jung et al 93 , Tang et al 94 , Goodier et al 95 , Petyuk et al 96 , Roux et al 97 , Castrogiovanni et al…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al 51 , Zhang et al 52 , Hartz et al 53 , Słomiński et al 54 , Johansson et al 55 , Pan et al 56 , Lopez-Sanz et al 57 , Grant 58 , Słomiński et al 59 , Galán et al 60 , Jordan et al 61 , Winkler et al 62 , Yip et al 63 , Crookshank et al 64 , Lempainen et al 65 , Qu and Polychronakos 66 , Morrison et al 67 , Zhang et al 68 , Gerlinger-Romero et al 69 , Belanger et al 70 , Dieter et al 71 , Wanic et al 72 , Ushijima Wanic et al 73 , Guo et al 74 , Davis et al 75 , Elbarbary et al 76 , Villasenor et al 77 , Zhang et al 78 , Lee et al 79 , Zhi et al 80 , Li Calzi et al 81 , Sebastiani et al 82 , Cherney et al 83 , Doggrell 84 and Yanagihara et al 85 studied the clinical and prognostic values of FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N -methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 in patients with T1DM. Vassilev et al 86 , Qin et al 87 , Ma et al 88 , West et al 89 , Hoffmann et al 90 , Deary et al 91 , Belangero et al 92 , Jung et al 93 , Tang et al 94 , Goodier et al 95 , Petyuk et al 96 , Roux et al 97 , Castrogiovanni et al…”
Section: Discussionmentioning
confidence: 99%
“…These findings were further confirmed in British, Chinese Han, and multinational Caucasian populations [ 26 , 50 , 51 ]. The association between BACH2 rs11755527 and T1D was then replicated among Pakistani patients but failed to be confirmed in Brazilians [ 32 , 52 ]. A former investigation of rs3757247 in adult T1D patients (mean age 33 ± 10 years) from Western Poland also revealed negative results, however, the studied cohort was limited to just 141 individuals hence that analysis could be underpowered to detect a minor effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the endocrine disorders, BACH2 variants were associated with adrenal and thyroid autoimmunity [ 25 28 ]. Data from T1D cohorts are unequivocal—genome-wide association studies pinpointed BACH2 polymorphisms as risk factors, while some local studies, including a small Polish series, failed to replicate this association [ 29 – 32 ]. With these in mind, our study was aimed to explore the genetic variant of the BACH2 gene, rs3757247, in autoimmune endocrine disease among Polish subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we investigated the biological functions of these DEGs by using online website, and GO and pathway enrichment analysis. Husemoen et al [52], Zhang et al [53], Hartz et al [54], Słomiń ki et al [55], Johansson et al [56], sPan et al [57], Lopez-Sanz et al [58], Grant, [59], Słomiń i et al [60], Galán et al sk [61], Jordan et al [62], Winkler et al [63], Yip et al [64], Crookshank et al [65], Lempainen et al [66], Qu and Polychronakos, [67], Morrison et al [68], Zhang et al [69], Gerlinger-Romero et al [70], Belanger et al [71], Dieter et al [72], Wanic et al [73], Ushijima Wanic et al [74], Guo et al [75], Davis et al [76], Elbarbary et al [77], Villasenor et al [78], Zhang et al [79], Lee et al [80], Zhi et al [81], Li Calzi et al [82], Sebastiani et al [83], Cherney et al [84], Doggrell, [85] and Yanagihara et al [86] found that FLG (filaggrin), FGF21, PEMT (phosphatidylethanolamine N-methyltransferase) KL (klotho), CEL (carboxyl ester lipase), FOSL2, STAT1, TCF7L2, TP53, EGFR (epidermal growth factor receptor), ETS1, KCNJ8, DEAF1, GCG (glucagon), IKZF4, OAS1, IRS1, ABCG2, FBXO32, PTBP1, BACH2, CNDP2, KLF11, MT1E, DPP4, SLC29A3, RGS16, MAS1, GCGR (glucagon receptor), HLA-C, VASP (vasodilator stimulated phosphoprotein), CCR2, PTGS2, GLP1R and JMJD6 are involved in the progression of T1DM. Vassilev et al [87], Qin et al [88], Ma et al [89], West et al [90], Hoffmann et al [91], Deary et al [92], Belangero et al [93], Jung et al [94], Tang et al [95], Goodier et al [96], Petyuk et al [97], Roux et al [98], Castrogiovanni et al [99], Suleiman et al [100], Haack et al [101], Kwiatkowski et al [102], Pinacho et al [103], Luo et al [104], He et al [105], Moudi et al [106], Thevenon et al [107], Li et al [108], Reitz et al [109], Jenkins and Escayg [110], Letronne et al [111], Ma et al [112<...>…”
Section: Discussionmentioning
confidence: 99%